Thermochemical heat recuperation for compressed air energy storage. (15th December 2021) - Lei, Fuqiong; Korba, David; Huang, Wei; Randhir, Kelvin; Li, Like; AuYeung, Nick
Highlights: Thermochemical recuperation is integrated into Advanced Compressed Air Energy Storage. Direct heat transfer is achieved between gas and solid. Both known and hypothetical redox reactions are considered. Thermochemical storage enables a more stable turbine inlet temperature. Longer storage durations and higher round trip efficiencies are possible. Abstract: Compressed Air Energy Storage (CAES) suffers from low energy and exergy conversion efficiencies (ca. 50% or less) inherent in compression, heat loss during storage, and the commonly employed natural gas-fired reheat prior to expansion. Previously, isothermal, and adiabatic (or 'advanced' adiabatic) compressed air energy storage have been proposed to enhance the efficiency of the process. Among the adiabatic schemes, thermal storage can be used to store heat from compression process. Prior to expansion, the air can recuperate the stored thermal energy, which could reduce or even eliminate the need for natural gas-fired reheat. Although sensible heat storage (SHS) and latent heat storage (LHS) have been previously investigated for this purpose, there are very few published studies looking at the use of thermochemical energy storage (TCES) for the CAES application. Here, a direct heat transfer scheme with combined thermochemical and sensible energy storage is proposed. The present study develops a mathematical model to address the conceptual design of the proposed idea. A detailed model and analysis are performed for TCES-rock-filled PBTES (packed bed filled with both barium oxides and rocks) and rock-filled PBTES. Results showed that similar round-trip efficiency (RTE) is achieved between rock-filled and TCES-rock-filled PBTES due to the relatively low heat capacity and heat of reaction for the barium oxides materials used in the current study. A 60% RTE is achieved for both systems with 20 h storage time after charge. However, with TCES material placed on top of the packed bed, a more stable turbine air inlet temperature (less than 200 K temperature variation) is obtained compared with all rock-filled packed bed (more than 300 K temperature difference) if idle time after charge is less than 20 h. In addition, with future advanced materials, the proposed idea could potentially improve the roundtrip efficiency of the process, have longer duration of storage and stable turbine air inlet temperature under suitable operating conditions. To better illustrate the potential of the concept, a hypothetical material with same heat capacity with rocks but a thermochemical storage capacity equal to three times that of barium oxides is investigated using the developed mode. Results showed that a potential of more than 5% RTE improvement could be obtained using the hypothetical material. Longer storage durations will increase the added value of the TCES. Additionally, 45% less volume is needed for the hypothetical-TCES-filled PBTES to achieve similar energy storage capacity as rock-filled PBTES with the case of 40 h idle time after charge. The concept could also be applied to Liquid Air Energy Storage.